1990
DOI: 10.1038/bjc.1990.26
|View full text |Cite
|
Sign up to set email alerts
|

An objective biochemical assessment of therapeutic response in metastatic breast cancer: a study with external review of clinical data

Abstract: Summary A series of tumour related markers have been examined in 179 patients receiving primary endocrine therapy for metastatic breast cancer. Significant correlations between therapeutic response (UICC criteria after 6 months of treatment) and appropriate alterations in serum concentrations of carcinoembryonic antigen, ferritin, c-reactive protein, orosomucoid and the erythrocyte sedimentation rate, have been observed when changes in these markers were examined only at high serum concentrations. By combining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
15
1

Year Published

1991
1991
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 26 publications
4
15
1
Order By: Relevance
“…We have confirmed that the biochemical index derived for patients receiving first-line endocrine therapy (Williams et al, 1990;Robertson et al, 1992) is also applicable to patients treated by chemotherapy. A highly significant correlation was observed between the 3 and 6 month UICC response assessments and changes in biochemical index (CEA, CA 15.3 and ESR) calculated after 6-8 and 12-16 weeks of chemotherapy.…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…We have confirmed that the biochemical index derived for patients receiving first-line endocrine therapy (Williams et al, 1990;Robertson et al, 1992) is also applicable to patients treated by chemotherapy. A highly significant correlation was observed between the 3 and 6 month UICC response assessments and changes in biochemical index (CEA, CA 15.3 and ESR) calculated after 6-8 and 12-16 weeks of chemotherapy.…”
Section: Discussionsupporting
confidence: 61%
“…The previously set cut-off values (see Table I) were used for all three markers (ie. CEA 6 ng ml-', CA 15.3 33 U ml-' and ESR 20 mm h-1); marker changes from the baseline value of > ± 10% were regarded as significant (Williams et al, 1990;Robertson et al, 1992). Using the three markers in combination 55 of 57 UICC assessable patients with systemic breast cancer were biochemically assessable (96%).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In Nottingham we have previously shown in a retrospective analysis (Williams et al, 1990) and prospectively confirmed (Nicholson et al, 1981;Nicholson et al, 1986 (Hayward et al, 1977). Three patients were unassessable for response by UICC criteria.…”
mentioning
confidence: 84%